(untitled) - Keomixay, Phoukham (Cần Thơ, 2019)
The investigations were carried out to study on the preparation dried vegetarian soup supplemented with mushroom and some legumes, and evaluate their nutritional, and sensorial properties, and quality change during storage of these products in different packages.
Keywords: Food industry and trade,Công nghiệp thực phẩm và thương mại